The analysis about the metastases to Gastrointestinal tract: a literature review, 2000-2023 - Sun, Ting-Ting; Liu, Fu-Guo (Frontiers in Oncology, 2025)
BackgroundCancers of the gastrointestinal tract exhibit a high detection rate, ranking as the fifth most common malignant tumor and the fourth leading cause of cancer-related death. In addition to primary malignant tumors of the gastrointestinal tract, secondary metastatic tumors significantly impact patient survival. The differentiation between primary and secondary gastrointestinal tumors remains a critical issue requiring further research and analysis.MethodsThis is a retrospective, observational study conducted from 2000 to 2023. We systematically searched the literature in PubMed, EMBASE, and COCHRANE databases from January 1, 2000, to November 31, 2023. Patients diagnosed with gastrointestinal (GI) tract metastasis were included in the study.ResultsA total of 165 patients were enrolled in this study. The most prevalent primary tumors were breast cancer (50.30%), renal cancer (16.96%), lung cancer (16.36%), melanoma (12.72%), and liver cancer (3.63%). The median interval between the diagnosis of the primary tumor and the detection of GI metastatic lesions was 8.53 years (range: 1–25 years). The most frequent endoscopic finding was a solitary mucosal or submucosal lesion situated in the gastric body. Metastases to extra-gastrointestinal organs were observed in the majority of patients. The integration of endoscopic biopsy with pathological and immunohistochemical analyses is essential for identifying the tumor origin. Surgical intervention in patients lacking extra-gastrointestinal metastases may improve prognosis.ConclusionsBreast, renal, lung, liver cancer, and melanoma were identified as the most frequent primary tumors. Clinical symptoms and endoscopic features were unable to predict the primary sites, which still require immunohistochemical analysis for accurate identification. The intervention modality and the presence or absence of distant metastasis significantly influenced patient prognosis.